Genotype–phenotype correlation in a large English cohort of patients with autosomal recessive ichthyosis. (1st March 2020) - Simpson, J.K.; Martinez‐Queipo, M.; Onoufriadis, A.; Tso, S.; Glass, E.; Liu, L.; Higashino, T.; Scott, W.; Tierney, C.; Simpson, M.A.; Desomchoke, R.; Youssefian, L.; et al.
Summary: Background: Recessive forms of congenital ichthyosis encompass a group of rare inherited disorders of keratinization leading to dry, scaly skin. So far, 13 genes have been implicated, but there is a paucity of data on genotype–phenotype correlation in some populations. Objectives: We compiled an English cohort of 146 individuals with recessive ichthyosis and assessed genotype–phenotype correlation. Methods: Deep phenotyping was undertaken by history‐taking and clinical examination. DNA was screened for mutations using a next‐generation sequencing ichthyosis gene panel and Sanger sequencing. Results: Cases were recruited from 13 National Health Service sites in England, with 65% of patients aged < 16 years at enrolment. Pathogenic biallelic mutations were found in 83% of cases, with the candidate gene spread as follows: TGM1 29%, NIPAL4 12%, ABCA12 12%, ALOX12B 9%, ALOXE3 7%, SLC27A4 5%, CERS3 3%, CYP4F22 3%, PNPLA1 2%, SDR9C7 1%. Clinically, a new sign, an anteriorly overfolded ear at birth, was noted in 43% of patients with ALOX12B mutations. The need for intensive care stay ( P = 0·004), and hand deformities ( P < 0·001), were associated with ABCA12 mutations. Self‐improving collodion ichthyosis occurred in 8% of the cases (mostly TGM1 and ALOX12B mutations) but could not be predicted precisely from neonatal phenotype or genotype. Conclusions: These data refine genotype–phenotype correlation for recessive forms of ichthyosis in England, demonstrating the spectrum of disease features and comorbidities, as well as the gene pathologies therein. Collectively, the data from these patients provide a valuable resource for further clinical assessment, improving clinical care and the possibility of future stratified management. What's already known about this topic? Recessive forms of ichthyosis are rare but often difficult to diagnose. Mutations in 13 genes are known to cause recessive forms of ichthyosis: ABCA12, ALOX12B, ALOXE3, CERS3, CYP4F22, LIPN, NIPAL4, PNPLA1, SDR9C7, SLC27A4, SULT2B1, ST14 and TGM1 . Some phenotypic features may associate with certain gene mutations, but paradigms for genotype–phenotype correlation need refining. What does this study add? The genotypic spectrum of recessive ichthyosis in England (based on 146 cases) comprises TGM1 (29%), NIPAL4 (12%), ABCA12 (12%), ALOX12B (9%), ALOXE3 (7%), SLC27A4 (5%), CERS3 (3%), CYP4F22 (3%), PNPLA1 (2%) and SDR9C7 (1%). New or particular phenotypic clues were defined for mutations in ALOX12B, ABCA12, CYP4F22, NIPAL4, SDR9C7 and TGM1, either in neonates or in later life, which allow for greater diagnostic precision. In around 17% of cases, the molecular basis of recessive ichthyosis remains unknown.